Elimination of chemical oxygen demand from domestic residual water by electrocoagulation with aluminum and iron electrodes - Aguilar Ascón, Edwar (2018)
This research determined the efficiency of removal of chemical oxygen demand (COD) by an electrocoagulation process. An electrocoagulation reactor with aluminum and iron electrodes was used to treat water from the treatment plant of the Research Center for Wastewater Treatment and Hazardous Waste. The COD removal percentage was a response variable for the experimental factorial design. The factors influencing the process were current intensity, treatment time, and pH. The best results in the percentage of removal of the COD were very similar to that obtained at a pH of 8.2 and 7, with values of 83% and 84%, respectively, with a current intensity of 7 A and a treatment time of 15 min. However, at 5 A and 10 min, values that exceed 80% removal were obtained. Statistical analysis indicates that only current intensity and time were significant for the response variable. Electrocoagulation is a viable process for the treatment of this type of effluent, in addition to being more versatile compared with biological processes.